Mastery of Quranic reading through j-QAF Programme among primary school pupils: a case study at Sek. Keb. Dato' Demang Hussin, Malacca - Nurfadilah Haji Mohamad
The j-QAF programme is an initiative introduced by the Ministry of Education (MOE) to strengthen the mastery of the basics of Islam to the pupils at the primary level. The programme which was introduced since 2004 includes aspects of learning Jawi script, reading the Quran, Arabic and basic skills of Fard ‘Ayn. In particular, this study is a case study on the level of Quranic reading mastery among pupils in Standard Six of first generation pupils who followed the teaching and learning in the j-QAF programme at Sek. Keb. Dato’ Demang Hussin, Malacca. The instruments used in this study were Quranic reading test which was conducted with 136 pupils and pupil interview. The data is analyzed through descriptive statistical methods including frequency, percentage, mean and standard deviation. In general, the findings indicate the level of proficiency and mastery of Quranic reading skills among respondents from the aspects of fluency, the rules of tajwid, pronunciation and punctuation marks. In addition, the study also proposed some recommendations to ensure successful implementation of the Quranic modules in the j-QAF programme in achieving its objectives.